Legislative shortcomings in the Iraqi Code of Criminal Procedure - Ghazi Faisal, Assistant Professor Dr. Haider (The college of law and political science journal, 2023)
As it is known, the purpose of drafting a law is to set the civilianrelationships among themselves in order on one hand and their relationshipto authority on the other; as legal texts are a mere expression of thelegislator’s volition, therefore, no matter the effort spent by the legislator,he cannot take note of the legal links that might take place in the futureto draft legal texts that would organize and manage it. For this reason, inRUGHUWRNHHS XSZLWKWKHFRQVWDQWVRFLHWDOFKDQJHV GHÀFLHQFLHVLQOHJDOWH[WVVKRXOGEHUHIRUPHGDQGUHFWLÀHGDQGVLQFHOHJDOWH[WVDUHPDQPDGH—and man is a fallible creature— one should not expect those legal texts toEHLPSHFFDEOH([DPSOHVRIWKRVHOHJLVODWLYHGHÀFLHQFLHVFDQEHIRXQGLQprocedural penal texts such as ambiguity, inconsistency which leaves noFKRLFHIRUWKHOHJLVODWRUEXWWRLQWHUIHUHLQRUGHUWRUHFWLI\WKRVHGHÀFLHQFLHV7KHVHGHÀFLHQFLHVDUHLQHYLWDEOHDQGDUHWKHQDWXUDOFRXUVHRIOLIHLQLWVQRQstatic and perpetual alteration and development. Therefore, no legal text cancontain them and no legislator can predict them unless by assumption; andassumption can be relatively small and limited